Violations of the Right to Health due to Limited Access to Protection of Health during the COVID-19 Pandemic in the Republic of Croatia and Possible Legal ImplicationsL - Mišić Radanović, Nina (Medicine, Law & Society, 2021)
The battle against the COVID-19 pandemic is still the most important problem and a great challenge for the overburdened health system in the Republic of Croatia. This paper examines the research into how violations of humans’ right to health occurred due to the inaccessibility to health protection for uninfected persons during the COVID-19 pandemic. The research implemented showed that a system of anti-epidemic measures which completely suspended or significantly reduced the possibility to access primary and hospital health care, stopped preventive programs of cancer detection. Much medical research has already revealed the possible harmful effects to people's health in the increase in cases of the contraction of and death from cancer and other serious illnesses, particularly in relation to certain vulnerable groups for example, women and oncology patients. The author concludes that the right to access protection of health during the COVID-19 pandemic in the Republic of Croatia was significantly limited and analyzes possible legal consequences which could occur due to the suspension or limitation to the right to access health care as a violation of the right to health.